(untitled) (Medico Legal Update, 2021)
This study aimed to identify the bullying experiences and coping patterns experienced by clinical nurses. A total of 215 nurses who had worked at 10 hospitals in Seoul from 3 September 2019 to 20 October participated, but two of them had missing data. Ultimately, 213 subjects were included. The collected data were analyzed using the SPSS/WIN20.O program which were analyzed using the mean and standard deviation. Subjects who experienced bullying accounted for 110 out of 213 (51.6%) in which 66.3% were experienced nurses and 21.8% were new nurses. To talk to a colleague was 57.3%, to work with a feeling of hurt but remain calm was 56.4%, to forget by thinking about something else or doing something was 50%. The study on the coping response after bullying has not been revealed in previous Korean reports, and it is expected to be a useful information for preventing workplace bullying in the future and establishing an immediate and active coping system.